Marine species conservation at CITES: How does media coverage inform or misinform?. (December 2021) - Shiffman, D.S.; Macdonald, C.C.; Wester, J.N.; Walsh, M.B.; Chevalier, A.; Kachelriess, D.; Friedman, K.J.
Abstract: Research into public perceptions of wildlife conservation and management can identify misunderstanding or bias and provide data needed to effectively target outreach with the goal of improving policy outcomes. This study identifies gaps and bias in media coverage of the Convention on International Trade in Endangered Species (CITES), an international agreement regulating trade in flora and fauna that attracts a significant amount of public attention, and that has in recent years increasingly incorporated protections for commercially exploited marine species. To examine one contributor to public understanding of processes and outcomes for marine species conservation at CITES, we performed a media content and discourse analysis for popular press articles from English-speaking newspapers worldwide (N = 102). Our analysis focused on how, and how often, marine species issues are discussed in the media, which experts are interviewed, which perspectives are highlighted, and whether important details and nuances known to experts are presented accurately (or at all). We show that proposals to list marine species on CITES appendices are discussed less often than proposals to list charismatic terrestrial species (e.g., elephants), and these proposals for trade controls on marine species are framed differently. Discussions centering on sharks and rays as a homogeneous group far exceed discussions of individual species, despite notably distinct risk profiles for different species. Extinction is rarely discussed and is poorly explained in the context of marine species. The contribution of marine species exploitation to local and global food security issues and fisher livelihoods is not discussed at all. Advocates from environmental non-profit groups dominate the list of interviewed experts, with alternative perspectives from groups linked to sustainable management like UNFAO (the United Nations agency with a fisheries mandate) and academics, rarely mentioned. Additionally, the fishing industry's perspective on issues surrounding the conservation of commercially exploited marine species is rarely represented. Recommendations for both follow-up research and practical steps to ensure a more balanced inclusion of the perspectives of key stakeholders are included.